Correlates of Protection for M Protein-Based Vaccines against Group A Streptococcus - Shu Ki Tsoi; Pierre R. Smeesters; Hannah R. C. Frost; Paul Licciardi; Andrew C. Steer (Journal of Immunology Research)
Group A streptococcus (GAS) is known to cause a broad spectrum of illness, from pharyngitis and impetigo, to autoimmune sequelae such as rheumatic heart disease, and invasive diseases. It is a significant cause of infectious disease morbidity and mortality worldwide, but no efficacious vaccine is currently available. Progress in GAS vaccine development has been hindered by a number of obstacles, including a lack of standardization in immunoassays and the need to define human correlates of protection. In this review, we have examined the current immunoassays used in both GAS and other organisms, and explored the various challenges in their implementation in order to propose potential future directions to identify a correlate of protection and facilitate the development of M protein-based vaccines, which are currently the main GAS vaccine candidates.